Parametric study on source rock potential of West Crocker Formation, onshore Sarawak: article / Muhammad Qayyum Azman, Nur Shuhadah Japperi and Norsyazwani Abdul Jalil - Azman, Muhammad Qayyum; Japperi, Nur Shuhadah; Abdul Jalil, Norsyazwani (2019)
West Crocker Formation is known with its lithologies and is described as a deep-water formation that is formed due to tectonic evolutions. Studies have show that West Crocker Formation has a good hydrocarbon generation and contain oil prone type II/III kerogen. It indicates that West Crocker Formation is a good source rock for petroleum accumulation and production. Thus, the purpose of this research paper is to determine the potential source rock of West Crocker Formation on onshore Sarawak. The methodology used in this research paper is by analyzing the source rock sample taken from the outcrop sample field using Gas Chromatographhy-Mass Spectrometry. From the result obtained, further analysis can be done in order to determine whether West Crocker Formation can be a good potential source rock or not.